2019
DOI: 10.3389/fpsyt.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Psychiatric Symptoms in Minimally Verbal Children and Adolescents With ASD

Abstract: Despite many studies documenting the prevalence of various co-occurring psychiatric symptoms in children and adults with ASD, less is known about how these symptoms relate to subtypes defined by particular phenotypic features within the ASD population. We examined the severity and prevalence of comorbid symptoms of psychopathology, emotion dysregulation, and maladaptive behaviors, as well as adaptive functioning, in a group of 65 minimally verbal children ( n = 33) and adolescents ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
(50 reference statements)
1
21
0
2
Order By: Relevance
“…For example, concurrent validity of the EDI was supported by positive correlations with measures of internalizing and externalizing symptoms (Child Behavior Checklist and Aberrant Behavior Checklist) in both ASD and non‐ASD samples [Mazefsky, Yu, & Pilkonis, 2020; Mazefsky et al, 2018,b]. Similar findings have been reported in other samples as well, such as a positive correlation between EDI scores and a measure of overall psychiatric burden in a sample of minimally verbal children and adolescents with ASD [Plesa Skwerer, Joseph, Eggleston, Meyer, & Tager‐Flusberg, 2019].…”
Section: Emotion Regulationsupporting
confidence: 56%
“…For example, concurrent validity of the EDI was supported by positive correlations with measures of internalizing and externalizing symptoms (Child Behavior Checklist and Aberrant Behavior Checklist) in both ASD and non‐ASD samples [Mazefsky, Yu, & Pilkonis, 2020; Mazefsky et al, 2018,b]. Similar findings have been reported in other samples as well, such as a positive correlation between EDI scores and a measure of overall psychiatric burden in a sample of minimally verbal children and adolescents with ASD [Plesa Skwerer, Joseph, Eggleston, Meyer, & Tager‐Flusberg, 2019].…”
Section: Emotion Regulationsupporting
confidence: 56%
“…The social and generalized worries align more with fears noted in a slightly older intellectual disability sample (i.e. ages 17–20, Forte et al, 2011), relative to a younger sample of youth with ASD and intellectual disability (i.e., ages 7–13; Kerns et al, 2020) and a minimally verbal sample of teens with ASD (age 12–18; Plesa Skwerer et al, 2019) which both indicated a preponderance of specific phobias. Semi‐structured anxiety interviews were not conducted in the present study and may have better differentiated specific anxiety disorders.…”
Section: Discussionmentioning
confidence: 81%
“…Adolescents with ASD and intellectual disability are a particularly complex and underserved subgroup of this population and are at significant risk for mental health disorders. Communication and behavioural difficulties can make the assessment of psychiatric comorbidity challenging (Jennett & Hagopian, 2008); however, there is an emerging recognition that psychiatric comorbidity may be the ‘norm’ in the ASD and intellectual disability population, including for adolescents described as minimally verbal (Plesa Skwerer et al, 2019). Anxiety occurs at higher rates in individuals with ASD and intellectual disability (53%) than in intellectual disability alone (17%; Bakken et al, 2010) with particular elevations noted in specific phobias (Gullone et al, 1996; Kerns et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, individuals with ASD often feel overwhelmed in loud, multisource settings [Alcántara, Weisblatt, Moore, & Bolton, 2004; Birch, 2003; Grandin, 1995], and overarousal may be related to overarching problems filtering targets from noise [Haigh, Heeger, Dinstein, Minshew, & Behrmann, 2015; Simmons et al, 2007; Vilidaite, Yu, & Baker, 2017]. Symptoms can vary in severity, but at least 30% of individuals with ASD meet the criteria for a secondary attention‐deficit/hyperactivity diagnosis [ Joshi et al, 2013; Plesa Skwerer, Joseph, Eggleston, Meyer, & Tager‐Flusberg, 2019]. Most research on attentional deficits in ASD has been conducted on verbally fluent participants with autism (ASD‐V), but recent studies suggest that attentional deficits are even more common in individuals who are minimally or low verbal in their language abilities [Lerner et al, 2018; Plesa Skwerer et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms can vary in severity, but at least 30% of individuals with ASD meet the criteria for a secondary attention‐deficit/hyperactivity diagnosis [ Joshi et al, 2013; Plesa Skwerer, Joseph, Eggleston, Meyer, & Tager‐Flusberg, 2019]. Most research on attentional deficits in ASD has been conducted on verbally fluent participants with autism (ASD‐V), but recent studies suggest that attentional deficits are even more common in individuals who are minimally or low verbal in their language abilities [Lerner et al, 2018; Plesa Skwerer et al, 2019].…”
Section: Introductionmentioning
confidence: 99%